Influence on mechanical properties of hot pressed, solution treated and age hardened 21-4N ODS alloy developed through pre-alloyed powders. (26th March 2020) - Mariappan, R.; Murali, Arun Prasad; Dharmalingam, G.; Prakasham, D. Siva
In the current study, mechanical properties of hot pressed, solution treated and aged austenitic stainless steels (21-4N) for were evaluated by varying the percentage of yttria addition. The milled powders were vacuum hot pressed at 1, 200°C with a pressure level of 56 MPa with a holding period of 2 hrs under the vacuum level of 10-2 torr. Hot pressed samples were solution treated at 1, 200°C for a period of 2 hrs and immediately subjected to water quenching to dissolve more grain boundary carbides. Further, to achieve the desired hardness samples were aged at 750°C held for 4 hrs followed by air cooling. Optical micrographs and SEM-EDS studies reveal austenitic grain with grain boundary carbides in the hot pressed condition. After solution treatment these precipitates disappears which was confirmed through SEM-EDS. Austenitic stainless steel containing 0.3 wt% yttria has attained higher tensile strength of 598 MPa in the age hardened condition.